Antibody-siRNA conjugates (ARC): Emerging siRNA drug formulation - Weiran Cao; Rui Li; Xing Pei; Meihong Chai; Lu Sun; Yuanyu Huang; Jiancheng Wang; Stefan Barth; Fei Yu; Huining He (Elsevier, 2022)
Antibody-drug conjugates (ADC) utilizing the targeting properties of antibodies and therapeutic effects of drugs have emerged a rapid development in recent years. However, the relatively low drug loading capacity of ADC systems commonly results in failure in delivering enough chemical drugs to the desired areas given a safe antibody dose, therefore the therapeutic efficacy of ADC systems is restricted. With the FDA approval of four siRNA drugs, patisiran, givosiran, lumasiran and inclisiran, the development of siRNAs has regained huge attention of researchers, where the design of delivery system for siRNAs is the key issue for further clinical applications. Inspired by the concept of ADC, the antibody-siRNA conjugates (ARC) have emerged as a potential vehicle for targeted siRNA drug delivery, with the ability to overcome the current obstacles in siRNA delivery. In this review, we summarized the efforts in the development of antibody-siRNA conjugates and hope to provide a basic view for researchers who are interested in this field.